2001
DOI: 10.1086/320352
|View full text |Cite
|
Sign up to set email alerts
|

The ASCA Catalog of Potential X‐Ray Counterparts of GeV Sources

Abstract: We present a catalog of 2-10 keV ASCA Gas Imaging Spectrometer images of fields containing bright sources of GeV emission. The images cover ∼ 85% of the 95% confidence position contour for 28 of the 30 sources with > 1 GeV fluxes above 4 × 10 −8 ph cm −2 s −1 . We find an excess of hard X-ray sources with F 2−10keV 10 −12 ergs cm −2 s −1 positionally coincident with unidentified sources of GeV emission. We comment on radio-loud and radio-quiet pulsar candidates, as well as several SNR and massive binaries as p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
108
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 90 publications
(111 citation statements)
references
References 42 publications
2
108
1
Order By: Relevance
“…The radio-quiet pulsar PSR J1826−1256 (P2), which powers the diffuse X-ray nebula PWN G018.5−0.4 (Roberts, Romani & Kawai 2001;Roberts et al 2007), may also be a candidate for the origin of HESS J1826−130. The distance d = 1.2 − 1.4 kpc suggested by Wang (2011) infers a TeV γ-ray efficiency ηγ ∼ 2 × 10 −4 which is at the lower end of typical ηγ values forĖSD ∼ 10 36−37 erg s −1 (Kargaltsev, Rangelov & Pavlov 2013).…”
Section: Other Potential Particle Acceleratorsmentioning
confidence: 99%
“…The radio-quiet pulsar PSR J1826−1256 (P2), which powers the diffuse X-ray nebula PWN G018.5−0.4 (Roberts, Romani & Kawai 2001;Roberts et al 2007), may also be a candidate for the origin of HESS J1826−130. The distance d = 1.2 − 1.4 kpc suggested by Wang (2011) infers a TeV γ-ray efficiency ηγ ∼ 2 × 10 −4 which is at the lower end of typical ηγ values forĖSD ∼ 10 36−37 erg s −1 (Kargaltsev, Rangelov & Pavlov 2013).…”
Section: Other Potential Particle Acceleratorsmentioning
confidence: 99%
“…Another suggested possibility has been that of a point- [42]), and Cygnus X-3. The center of gravity with statistical errors and intrinsic size (standard deviation of a 2-dim Gaussian, σsrc) are indicated by the white cross and white circle, respectively.…”
Section: Tev J2032+4130mentioning
confidence: 99%
“…The source with the highest V 12 value in the Galactic plane without a potential Blazar identification is GeV J1809−2327. An X-ray nebulae was discovered in its error box with ASCA (Roberts et al, 2001) which subsequent Chandra and VLA imaging showed to be a RPWN (Braje et al, 2002). An XMM-Newton EPIC-PN observation, which was unfortunately taken in small window mode, suggests a fainter X-ray halo surrounding the X-ray trail seen in the short Chandra exposure, strongly reminiscent of the Mouse (Fig.…”
Section: Rapidly Moving Pulsar Wind Nebulae Associated Withmentioning
confidence: 99%